STUDI PENDAPATAN DAN POLA BAGI HASIL NELAYAN PUKAT PAYANG YANG MENGGUNAKAN ALAT BANTU RUMPON - Hafinuddin Hafinuddin; Nilam Shantica; Syarifah Zuraidah (Universitas Teuku Umar, 2019)
Rumpon (fish aggregating device) is a tool for fisherman to catch fish in the sea. This research aims to know income level and plural by used sharing profit of seine net (pukat payang) with fish aggregating devices (FADs). This study have done on Agustus-September 2016, at fish landing of Ujong Baroh (PPI Ujong Baroh) district of West Aceh. Survey method was used for this study analysis of data is using deep profit analysis with to considering investment value and cutback and also descriptive analysis. Income per month for each fisherman is Rp. 2.642.776,3,-; ship-owner (Toke Boat) Rp. 29.599.095,6,-; wholesaler (Toke Bangku) Rp. 7.399.774,-. Percentage of sharing profit at fish landing of ujong Baroh is for ship-owner 40%, fisherman 50% and wholesaler 10%. FAD using for seine net show expected to increasing profit for fisherman of boat seine.